IMPACT OF BUSINESS PERFORMANCE AND TOTAL QUALITY MANAGEMENT ON THE SMALL AND MEDIUM ENTERPRISES OF MEXICO - Vargas-Hernández, José G; Vázquez Lerma, Vanessa Yesenia (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The purpose of this research is to analyze the degree of effectiveness of Total Quality Management (TQM) in small and medium enterprises (SMEs) in Mexico as a function of Business Performance, considering that Business Performance is related to Total Quality Management. This research is analytical and descriptive since no statistical method is used, only the variables and the research problem are analyzed in detail and in a detailed manner, and descriptive because tables and tables can be found to help facilitate understanding of these important concepts. This research will analyze the impact of both variables, and with this, the entrepreneurs can make the necessary changes in their production line or in their employees to obtain better and greater positive results.